Respuesta :
Plug (3y-7) into the second equation as x.
3(3y-7)+y=-1
Now solve it like a regular equation!
First, distribute the 3 into (3y-7)
9y-21+y=-1
Combine the like terms
10y-21=-1
Now, add 21 to both sides of the equation.
10y=20
Finally, divide each side by 10.
y=2
Plug 2 into the first equation as y.
x=3(2)-7
x=6-7
x=-1
To check your answer, plug x and y into the second equation.
3(-1)+2=-1
-3+2=-1
-1=-1
x=-1
y=2
Hope this helped! :)
3(3y-7)+y=-1
Now solve it like a regular equation!
First, distribute the 3 into (3y-7)
9y-21+y=-1
Combine the like terms
10y-21=-1
Now, add 21 to both sides of the equation.
10y=20
Finally, divide each side by 10.
y=2
Plug 2 into the first equation as y.
x=3(2)-7
x=6-7
x=-1
To check your answer, plug x and y into the second equation.
3(-1)+2=-1
-3+2=-1
-1=-1
x=-1
y=2
Hope this helped! :)